Determinants of the deterioration in China’s public finances in 2005-2018 - Twarowska, Katarzyna (Czynniki wpływające na pogorszenie stanu finansów publicznych w Chinach w latach 2005-2018, 2019)
The aim of the paper is to assess the condition of China’s public finances, identify the main factors that contribute to the increase in public debt, and to provide some suggestions that could be considered to improve the quality of public finances and reduce systemic risk. To achieve the objective of research the descriptive comparative method was used. The analysis was carried out for the period 2005-2018, however, due to the special conditions for the development of the Chinese economy, the background from previous years is also presented, as well as forecasts up to 2024. The analysis allowed to formulate conclusions, the most significant of which are that the main causes of China’s debt problem and the rising systemic risks are the effect of the global financial crisis and the change of the economic growth strategy to a strategy based on internal demand, which results in fiscal expansion. A particularly troubling development is the pace of growth in public debt, in particular the increase in local government debt and the increase in the share of short-term financing in external debt
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 114-128